The Vibro-Impact Response of Heat Exchanger U-Bend Tubes with Flat Bar Supports - Yetisir, Metin (My University, 1985)
A theoretical study has been conducted to investigate the effect of flat bars supports on the dynamic response of a heat exchanger U-tube. The tube is modelled using three dimensional, six degrees of freedom per node straight beam finite elements. A new method, the stiffness method, is introduced to compute the impact forces at the supports. It is compared with the previously used external force method. Modal analysis is employed to investigate the modal energy dissipation in the higher modes. Time response of the U-tube is analysed using a Fast Fourier Transform algorithm. The effects of clearance, excitation magnitude, and mode coupling through friction at the supports are investigated.
Keywords: heat exchanger U-tube; flat bar support; stiffness method; external force; modal energy dissipation; Fast Fourier Transform